2017
DOI: 10.13083/reveng.v25i6.687
|View full text |Cite
|
Sign up to set email alerts
|

Effective Microorganisms (Em) as Biofeeders for Anaerobic Digestion

Abstract: Soil micro-organisms called Effective Microorganisms (EM) were first cultivated and used in the 1970s. Researches about these cultures have since then demonstrated their effectiveness in improving soil characteristics and as an alternative for accelerating organic matter decomposition in waste treatment systems. The objective of this study was to test whether the addition of EM to substrates incubated in anaerobic digesters would increase the efficiency of waste treatment and biogas production. EM cultures we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…Our results also agreed with the results of another local study (12), which used the product to improve food conversion and weight gain, they also used the product at 1% and noted that the use of the product and within this concentration had significant results in improving food conversion and weight gain and increasing the length of the villi in the jejunum and increasing the number of goblet cells. Also, a recent study (17) indicated that the use of this product with a concentration of 1% may be useful in anaerobic fermentation for the disposal of organic matter and waste.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results also agreed with the results of another local study (12), which used the product to improve food conversion and weight gain, they also used the product at 1% and noted that the use of the product and within this concentration had significant results in improving food conversion and weight gain and increasing the length of the villi in the jejunum and increasing the number of goblet cells. Also, a recent study (17) indicated that the use of this product with a concentration of 1% may be useful in anaerobic fermentation for the disposal of organic matter and waste.…”
Section: Discussionmentioning
confidence: 99%
“…Effective microorganisms are a mixture of microorganisms that are harmless, non-pathogenic, nongenetically modified, and finally chemically non processed (9). The technology of EM has been used in wide zones, it has been used in the poultry industry (10-12), improved agricultural crops (13)(14)(15), sewage treatment (16,17), increased production efficiency and removal of toxic substances especially in fishes farms (18), disposal of food waste and modified it for composting (19,20), and improvement of forest soils (21).…”
Section: Introductionmentioning
confidence: 99%